Abstract 106: CHANTER Syndrome: A Case Report Of A 59 Year Old Man With Positive Outcome - Sherif Elsayed; Mina Al‐Ani; Anvesh Balabhadra; Ahmed Elmashad (Stroke: Vascular and Interventional Neurology)
Introduction Cerebellar, Hippocampal, and Basal Nuclei Transient Edema with Restricted Diffusion (CHANTER) syndrome was first described in 2019 [1] as a pattern of radiographic findings that are distinct from ischemic, anoxic, or toxic brain injury. Pathophysiology is still uncertain, but some proposed theories include a primary metabolic etiology or a mitochondrial failure of gray matter. Clinically, patients typically present with altered level of consciousness. Radiographically, diffusion weighted imaging shows restriction in the bilateral hippocampi, bilateral cerebelli, and basal nuclei. The cerebral cortex, thalamus, and subcortical white matter are usually spared. Despite the morbid clinical picture on presenation, positive outcomes were reported with early intervention. We describe a case of CHANTER syndrome in a 59 year old man with history of illicit substance abuse. Methods Case report with electronic medical record review. Results 59‐year‐old man with history of illicit substance abuse including cocaine, opioid, and phencyclidine presented to the hospital after being found down at a drug store. Patient did not respond to Naloxone and was eventually intubated due to respiratory compromise. Non‐contrast CT head showed hypoattenuation of the bilateral cerebellar hemispheres with mild effacement of the fourth ventricle. MRI brain showed diffusion signal abnormalities with corresponding T2 FLAIR hyperintensities in the bilateral cerebellar hemispheres, bilateral hippocampi, and bilateral basal ganglia with some involvement of the left occipital lobe suggestive of CHANTER syndrome. As vasogenic edema worsened, hydrocephalus ensued requiring administration of hypertonic saline and eventual external ventricular drain (EVD) insertion in the neurocritical care unit. Despite initial improvement in his level of consciousness after the EVD insertion, his intracranial pressure (ICP) continued to increase and midazolam and ketamine infusion drips were added. A fine balance between lowering the ICP and avoiding respiratory suppresion with sedating infusions was maintained. Consecutive MRI brain images over the course of the following 4 weeks of his stay showed decrease of the abnormal diffusion weighted imaging signal along with improvement in his overall mental status and eventual discharge 12 weeks from his initial presentation. Conclusion This case further strengthens the relationship between CHANTER syndrome and illicit substance use as a likely etiology along with other cases in the literature. Aggressive management in the neurocritical care to control vasogenic edema and avoid ICP elevation is essential to give patients the highest chance of recovery. Clinical improvement At least partial reversal of the radiographic findings of CHANTER syndrome can be attained with treatment, however, unclear if complete reversal is possible.